«PETRIJI J DOVBUSCHUKY» IN QUANTITATIVE COMPARISON WITH THE GREAT PROSE OF IVAN FRANKO - BUK, Solomija (Linguistic and Conceptual Worldviews, 2022)
The article is devoted to the linguistic and statistical study of the dictionary and text of I. Franko’s novel "Petriji j Dovbuschuky", second eddition (1909-1912). In the process of complex system corpus lexicographic and linguistic- statistical description of the long prose fiction by I. Franko, twelve most important statistical parameters were identified. They were applied to characterize the novel "Petriji... " consistently: 1) the size of the text, 2) the size of the dictionary of tokens; 3) richness of vocabulary, 4) average word repeatability in the text, 5) number of Hapax legomena (words with frequency 1), 6) index of text exclusivity, 7) index of dictionary exclusivity, 8) number of high-frequency vocabulary in the text, 9) number of high-frequency vocabulary in the dictionary, 10) index of concentration in the text, 11) index of concentration in the dictionary, 12) morphological statistical characteristics: the number of every part of speech in the dictionary and text, 13) index of epithetization, 14) index of verb modifiers, 15) index of nominalization, 16) the ratio of direct and author’s speech (index of dialogicity). In comparison with other works of long prose fiction by I. Franko, the most explanatory parameters were the morphological characteristics of the index of epithetization and index of verb modifiers, as well as textual characteristic such as the index of dialogicity. The applied classical and original interdisciplinary approaches, as well as the electronic text corpus of "Petriji." can serve as an empirical basis for further linguistic, literary, cultural, historical studies on this text.